‘Free Huey or the Sky’s the Limit’: The Black Panther Party and the Campaign to Free Huey P. Newton - Joe Street (European Journal of American Studies)
In October 1967, the co-founder of the Black Panther Party for Self-Defense, Huey P. Newton was arrested and charged with the murder of a police officer. His organization, which was on the point of collapse, rallied around him, courtesy of a major campaign that ran through his trial and his two years in prison, making ‘Free Huey’ a rallying cry for radicals across the globe. It transformed the BPP into one of the most visible political organizations of the era whilst redefining Newton as one of the key icons of 1968. As important, the ‘Free Huey’ campaign enabled the BPP to surf 1968’s radical tide, forging links with other radical groups as it grew to international prominence. Yet this newfound fame was not unproblematic, since it revealed the ambiguities of the BPP’s philosophy and elevated Newton to mythic proportions that no living human could match. The ‘Free Huey’ campaign thus reveals both the ability of radical groups to generate and exploit the revolutionary fervor of the year and the problems inherent in such an approach.